EVALUASI KINERJA PEMERINTAH KOTA PEKANBARU BERBASIS PERSEPSI MASYARAKAT - HAYATUN NUFUS; SUFIAN HAMIM; Rosmayani Rosmayani; Raden Imam Al hafis (Journal of Innovative and Creativity (Joecy), 2026)
The performance of local governments is a key indicator for assessing the quality of public services and the implementation of good governance principles. This study aims to evaluate the performance of the Pekanbaru City Government based on public perceptions. A descriptive quantitative approach was employed, using public perception survey data analyzed through tabulation and descriptive interpretation. The findings indicate that respondents’ perceptions of public service performance, service institutions, service governance, and the overall performance of the Pekanbaru City Government are generally dominated by positive assessments. However, several aspects still require serious attention, particularly government performance in the economic and infrastructure sectors. Therefore, this study recommends that the Pekanbaru City Government not only maintain its positive achievements in basic public services but also strengthen the governance of economic and infrastructure policies and enhance public communication to ensure that the benefits of development are more widely and equitably experienced by the community.